Influence of the Online Environment on Developing Communicative Sensitivity in Students - Paluanova, Xalifa (The Lingua Spectrum, 2025)
This article argues that digital learning environments – telecollaboration, computer-mediated communication, gameful scenarios, VR/AR, and conversational agents – create fertile conditions for developing learners’ pragmatic awareness and competence. Mechanisms include dense, contextualized input; opportunities to notice stance and politeness in real time; immediate, data-informed feedback; and reflection supported by learner corpora and replayable logs (Kasper & Rose, 2002; Taguchi, 2015; Sykes & Reinhardt, 2013). Design matters: tasks should target speech acts, turn-taking, indexicality, and register alignment with a clear skopos; assessment should combine scenario-based tasks, online role-plays, and web-delivered pragmatic tests rather than rely on discourse-completion alone (Roever, 2005; Bardovi-Harlig, 2013). Risks – platform norms, culture-blind rubrics, and algorithmic bias – are mitigated by explicit style guides, intercultural briefing, and corpus-anchored reflection. The conclusion frames digital environments as pragmatic laboratories where learners rehearse social action, shifting from “knowing forms” to “doing things with words” in multilingual ecologies (Ishihara & Cohen, 2010; Chapelle, 2001).